2012
DOI: 10.1111/j.1741-3737.2012.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Widowhood on Parent–Child Relations: Does Parents' Personality Matter?

Abstract: The authors evaluated the extent to which the short-term effect of late life widowhood on parent -child relationships is moderated by 5 personality traits-Extraversion, Agreeableness, Conscientiousness, Emotional Stability, and Openness to Experience-and how these interactive effects differ by gender. Data were from the Changing Lives of Older Couples Study ( N = 1,532). The results indicated that the effects of widowhood on positive and negative interactions with children were significantly moderated by Agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Earlier work (Pai and Ha 2012; Utz et al 2004) has shown that widowed adults often rely on their adult children for support in the period following widowhood. Relationships with and support from siblings may also be important: from a lifetime perspective, siblings have a central position in individuals' networks and are thought to again become important towards the end of the lifecourse as long-lived relationships (White 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work (Pai and Ha 2012; Utz et al 2004) has shown that widowed adults often rely on their adult children for support in the period following widowhood. Relationships with and support from siblings may also be important: from a lifetime perspective, siblings have a central position in individuals' networks and are thought to again become important towards the end of the lifecourse as long-lived relationships (White 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Adult children and siblings are particularly suited to undertake part of the deceased spouse's tasks and duties and contend with the griefrelated and practical needs of the widowed spouse. Friends and other age-peers add companionship, advice, and encouragement, and neighbors contribute assistance with daily living as they live nearby (Ha, 2008;Isherwood et al, 2017;Pai & Ha, 2012;Zettel & Rook, 2004). At the same time, few terminations are likely for relationships that are mainly maintained via the deceased spouse, such as common friends or in-laws.…”
Section: Variations In Compensationmentioning
confidence: 99%
“…On average, the number of close relationships, frequency of contact and interaction, and support received from others increase after bereavement, or at least remain stable (Dean et al, 1992;Donnelly & Hinterlong, 2010;Kalmijn, 2012), whereas immediately after the event, widows and widowers tend to intensify long-standing and very close relationships with their children (Guiaux et al, 2007;Isherwood et al, 2017;Roan & Raley, 1996;Scott et al, 2007). Later on, friends, wider kin, and new relationships gain in importance (Ha, 2008;Pai & Ha, 2012;Zettel & Rook, 2004) including growing engagement in volunteering activities (Li, 2007). Increases are, however, of temporary nature, as between the third and the fifth post-widowhood year, gains in social participation and support plateau and then begin to decrease, reaching pre-loss or even lower levels in the long-run (Ferraro & Barresi, 1982;Ferraro et al, 1984;Guiaux et al, 2007).…”
mentioning
confidence: 99%
“…In addition, emotionally stable and conscientious personality trait in caregivers protected the children from being aggressive (van Aken et al, 2007;Oliver et al, 2009). In terms of the relationship quality between caregivers and their children, a differential effect of the widowed parents' personality traits was found (Pai and Ha, 2012). Specifically, they found that widowed parents with an agreeable personality had more positive interactions, while those with extraversion or openness to experience had more negative interactions with their children.…”
Section: Introductionmentioning
confidence: 96%
“…Caregivers' characteristics and attitudes have been suggested to moderate both executive function (e.g., Schroeder and Kelley, 2010;Valcan et al, 2018;Hughes and Devine, 2019) and aggression (e.g., Sulik et al, 2015;Jung et al, 2018) as well as the relationship quality with their children (e.g., Pai and Ha, 2012). These findings suggested that positive caregivers' factors (e.g., parental warmth and attitudes to the child) protected children and adolescents from executive function deficits and aggressive problems.…”
Section: Introductionmentioning
confidence: 98%